Factors associated with delirium in mechanically ventilated patients in Medical Intensive Care Units - Inchai, Juthamas; Theerakittikul, Theerakorn; Peerapornratana, Sadudee (Biomedical Sciences and Clinical Medicine, 2018)
Background Delirium is a condition frequently found among hospitalized patients, particularly those in an intensive care unit (ICU) setting. Recent studies in Western and Asian countries have shown that delirium in ICU patients is associated with multiple complications and adverse outcomes. Objective To explore factors associated with delirium in mechanically ventilated patients in intensive care units, outcomes of delirium on 30-day all-cause mortality, and length of ICU and hospital stay. Methods A prospective cohort study was conducted in the medical and coronary ICUs at a tertiary care, university-based hospital. The subjects were adult patients undergoing mechanical ventilation who had been admitted to the medical or coronary ICU from May through August, 2012. All patients were assessed for delirium using the Thai version of the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU). Patient outcomes, including duration of stay in the ICU and in the hospital and 30 day mortality were compared between patients with delirium and delirium-free patients. Results Of a total of 60 patients enrolled and followed during their ICU admission, 10 (16.67%) developed delirium. The patients with delirium had a longer duration of hospital and ICU stay (32 days vs. 10.5 days, p=0.001; 12.5 days vs. 3 days, p<0.001, respectively). The development of delirium was associated with higher dosages of fentanyl (OR 10.68; 95% CI, 1.59–71.84) and reintubation (OR 97.14; 95% CI, 3.51– 2685.49). Conclusion Delirium in mechanically ventilated patients in a medical ICU is associated with prolonged hospital and ICU stay. Independent risk factors for developing delirium include the accumulative dosage of fentanyl and reintubation.